2021
DOI: 10.1007/s12020-021-02952-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of Graves´ophthalmopathy in patients with increasing TRAb after radioiodine treatment and the impact of CTLA4 on TRAb titres

Abstract: Introduction Treatment of Graves´ disease (GD) with radioiodine increases the risk of developing Graves´ ophthalmopathy (GO), and the link between thyroid and orbital tissue may be the presence of TSH-receptors. Radioiodine increases the titers of TRAb and the aim was to investigate the relationship between GO and TRAb titers after treatment with radioiodine and to define the impact of risk genes. Methods GD patients without ophthalmopathy or previous trea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, a phenomenon is observed that contradicts the claim in this paper. This paper says that TRAb level decreases when the high TH level recovers to normal, but it is observed that after radioiodine treatment TRAb temporarily increases and that transient increase in TRAb is associated with the deterioration and the onset of the grave´s ophthalmopathy [26]. The exact cause for that is not yet clear, but the following reasons are possible:…”
Section: Discussionmentioning
confidence: 99%
“…However, a phenomenon is observed that contradicts the claim in this paper. This paper says that TRAb level decreases when the high TH level recovers to normal, but it is observed that after radioiodine treatment TRAb temporarily increases and that transient increase in TRAb is associated with the deterioration and the onset of the grave´s ophthalmopathy [26]. The exact cause for that is not yet clear, but the following reasons are possible:…”
Section: Discussionmentioning
confidence: 99%
“…Regarding GD, it should be emphasized that the CTLA-4 gene is recognized as the most important genetic factor in the development of this pathology, from the perspective of the presence of the A22G point mutation in the CTLA-4 gene [50]. In addition, it is established by researchers in the field that the G/G genotype in the CTLA-4 gene, the A22G polymorphism is an important risk factor for HT-associated ophthalmopathy [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…TRAbs are the diagnostic marker for Graves’ disease, and monitoring pretreatment levels and levels before ceasing therapy provides valuable prognostic information [ 12 ]. High pretreatment TRAb levels are associated with less response to anti-thyroid drugs and higher rates of disease recurrence [ 13 ] as well as a risk of developing Graves’ ophthalmopathy [ 14 , 15 , 16 ]. TRAb levels are measured before cessation of treatment because patterns in TRAb changes can predict the risk of recurrence and guide further management [ 4 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%